The Mediating Role of Brand Awareness, the Influence of Social Media Marketing, on Purchase Intention of Jolted Coffeeshop & Eatery Products in Gianyar Regency - I Made Arditya Jaya; Putu Yudi Setiawan (Indonesian Journal of Business Analytics, 2025)
Modern coffee shops and cafes have grown in many places, including Gianyar Regency, Bali, as a result of the advent of the digitalization era, which is characterized by the quick use of social media as a marketing tool and the rising consumption of coffee, which is now a part of people's lifestyles. This study sought to ascertain how brand awareness mediated the impact of social media marketing on Gianyar Regency consumers' propensity to buy Jolted Coffee Shop & Eatery items. Purposive sampling combined with non-probability sampling was the methodology employed. A survey method was used to collect data, and 120 respondents were given questionnaires. Structural Equation Modeling-Partial Least Squares (SEMPLS) analysis was the method employed. The findings demonstrated that social media marketing significantly and favorably influenced both brand awareness and purchase intentions, that brand awareness significantly and favorably influenced purchase intentions, and that brand awareness was able to mediate the impact of social media marketing on purchase intentions. The management of Jolted Coffee Shop & Eatery may increase purchasing intentions for its products by using social media marketing and brand awareness, which is made possible by the practical use of this research as a guide.